PENTINGNYA PENYULUHAN PEMILU DALAM MENJAGA PARTISIPASI PEMILIH PEMULA MENUJU PEMILIHAN BERINTEGRITAS - Asnawi, Asnawi; Rahayu, Luis Fiska; Maulana, Ayang Fristia; Ramadhan, Muhamad Naufal; Salsabila, Anisa Rama; Hapidin, Lukman; Sabila, Dewita (Jurnal Abdimas Bina Bangsa, 2024)
This study discusses the crucial role of young voters in upholding the integrity of the upcoming simultaneous elections in 2024 in the village of Kelapian. The research identifies the positive impact of active participation by young voters on the honesty of the elections and the stability of democracy. Using a qualitative approach, data was gathered through in-depth interviews and document analysis. The results indicate that young voters have the potential to mitigate dishonest practices in elections by playing a role in social oversight. Their engagement can promote transparency, accountability, and wider participation in the political process. Therefore, this research highlights the necessity of effective political education for young voters, as well as collaborative efforts among the government, society, and stakeholders to maintain election integrity. The findings of this study are expected to provide guidance for strategic planning to enhance awareness and involvement of young voters in preserving election honesty